Satellite Heat Transfer Control Using a Nonlinear PI Method - Poorahangaryan, Fereshte (Mechanical Technology and Engineering Insights, 2024)
Thermal control in satellites is a critical discipline that maintains allowable temperature conditions across all subsystems. Satellite thermal regulation can be achieved through various approaches, which are broadly classified into passive and active methods. In passive control, thermal conditions are managed using passive elements such as coatings, insulation, radiators, and similar components. In contrast, active control typically employs closed-loop systems with temperature feedback. In this paper, the design of an active thermal control system for an Earth-orbiting satellite is carried out using a Nonlinear Proportional–Integral (NPI) control strategy. In this approach, the temperature of each subsystem is considered as a state variable, while heaters are modeled as actuators. Through comparative analyses, it is demonstrated that, due to actuator saturation effects, the nonlinear PI controller exhibits superior performance compared to the classical Proportional–Integral (PI) method, particularly in reducing overshoot and settling time.